2021
DOI: 10.1101/2021.08.26.457753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NF-κB-Inducing Kinase Maintains Mitochondrial Efficiency and Systemic Metabolic Homeostasis

Abstract: Obesity is a predominant risk factor for metabolic syndrome, which refers to a cluster of disorders that include diabetes, cardiovascular disease and fatty liver disease. Obesity and overnutrition are associated with aberrant immune and inflammatory responses resulting in increased local fat deposition, insulin resistance and systemic metabolic dysregulation. Here we show NF-κB-inducing kinase (NIK), a critical regulator of immunity and inflammation has local and systemic effects on metabolic processes. We dem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…We have recently observed that NIK KO mice exhibit altered systemic metabolism characterized by an increase in aerobic glycolysis and impaired respiration (32), which is similar to patients with primary mitochondrial diseases (MD) caused by mutations in OXPHOS genes. Patients with MD often experience recurrent infections and display adaptive immunodeficiency (39,40), paralleling those with NIK loss-of-function PID.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We have recently observed that NIK KO mice exhibit altered systemic metabolism characterized by an increase in aerobic glycolysis and impaired respiration (32), which is similar to patients with primary mitochondrial diseases (MD) caused by mutations in OXPHOS genes. Patients with MD often experience recurrent infections and display adaptive immunodeficiency (39,40), paralleling those with NIK loss-of-function PID.…”
Section: Discussionmentioning
confidence: 96%
“…How loss of NIK function alters innate immune cell development and function in patients with PID is unclear, and the impact of NIK dysregulation on immunometabolic homeostasis in PID has not been previously considered. We have recently observed that NIK KO mice exhibit altered systemic metabolism characterized by an increase in aerobic glycolysis and impaired respiration (32), which is similar to patients with primary mitochondrial diseases (MD) caused by mutations in OXPHOS genes. Patients with MD often experience recurrent infections and display adaptive immunodeficiency (39, 40), paralleling those with NIK loss-of-function PID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B022 has also been used to treat mice in the context of alcoholic liver disease, where it alleviated alcoholic steatosis, yet toxicities remain unclear ( 82 ). Finally, in vitro B022 treatment of mouse stem cells prevented adipogenesis and inhibited non-canonical NF-κB signaling ( 86 ). Although these cells do not show nuclear canonical NF-κB, B022 treatment did reduce cytoplasmic RelA phosphorylation levels.…”
Section: Overview Of In Vivo Nik Inhibitorsmentioning
confidence: 99%